Music, rhythmic gymnastics and expressiveness: an artistic performance - Maria Gabriel morgado; Maria Beatriz Licursi; Levi Leonido (Desafio Singular, 2022)
In rhythmic gymnastics, we appreciate the brilliant success in a true performing art whose sensitively expressive movements of great technical skill integrated into the music result in an exquisite and refined performance that involves body plasticity, musical receptivity, feelings and emotions. The practice of gymnastics significantly contributes to the development of body movements and musicality, boosting motor and artistic abilities by the acquisition of improved skills for jumping, running and practising different exercises. This study aimed to investigate how music is important in the development of rhythmic gymnastics. A literature review was carried out with research from 2016 to 2021 and published in Google Academic. We emphasise how the body action perfectly integrated into the music is essential for the artistic representation of an enchanting plastic, musical and grandiose beauty. We understand that encouraging physical exercise, especially artistic rhythmic gymnastics, is very important for the development of essential qualities for the individual, such as physical, behavioural, artistic and emotional attributes.